PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia tahun 2019 – 2020) - Muchammad Dava Rachmawan; Umaimah (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to examine the effect of corporate social responsibility and capital intensity on tax evasion by using research samples of mining sector companies listed on the Indonesia Stock Exchange in 2019 - 2020. The taxes levied by the state function as the main source aiming to finance public expenditures and function as a tool to regulate and implement policies in the social and economic fields and to be used for the greatest prosperity of the people and the people. The phenomenon of tax avoidance in Indonesia can also be seen from the tax ratio (Tax Ratio). Tax collection performance can be seen from the ratio of taxes collected by the state. Tax avoidance is a saving on the amount of tax payable, individual and corporate taxpayers use the weak points of existing tax rules, in carrying out their tax management. Tax avoidance is also associated with tax planning, both of them use legal means to reduce or even eliminate tax obligations, but from a tax policy point of view, neglecting tax avoidance practices can result in injustice and reduced efficiency of a tax system. . The results obtained from this study are that corporate social responsibility has a negative effect on tax evasion. Meanwhile, capital intensity has no effect on tax evasion. This study uses a quantitative approach. This test is done with linear regression